2014
DOI: 10.1002/chem.201403758
|View full text |Cite
|
Sign up to set email alerts
|

Dissymmetrical U‐Shaped π‐Stacked Supramolecular Assemblies by Using a Dinuclear CuI Clip with Organophosphorus Ligands and Monotopic Fully π‐Conjugated Ligands

Abstract: Reactions between the U-shaped binuclear Cu(I) complex A that bears short metal-metal distances and the cyano-capped monotopic π-conjugated ligands 1-5 that carry gradually bulkier polyaromatic terminal fragments lead to the formation of π-stacked supramolecular assemblies 6-10, respectively, in yields of 50-80 %. These derivatives have been characterized by multinuclear NMR spectroscopic analysis and X-ray diffraction studies. Their solid-state structures show the selective formation of U-shaped supramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 128 publications
0
16
0
Order By: Relevance
“…We first decided to evaluate the possibility of synthesizing an ynamide conjugated with a polycyclic aromatic structure, namely a benzophenanthrene, and to react it with TCNE to obtain derivative 1 a (Figure ). To this end, compound 2 a was prepared according to a described procedure and reacted with N ‐bromosuccinimide (NBS) in the presence of a catalytic amount of silver nitrate to give carbo[4]helicene‐ethynyl bromide 3 a in 77 % yield (Scheme , top). Compound 3 a was then subjected to Hsung conditions to form ynamide 4 a in a modest 26 % yield (unoptimized due to the very low solubility of 3 a ).…”
Section: Resultsmentioning
confidence: 99%
“…We first decided to evaluate the possibility of synthesizing an ynamide conjugated with a polycyclic aromatic structure, namely a benzophenanthrene, and to react it with TCNE to obtain derivative 1 a (Figure ). To this end, compound 2 a was prepared according to a described procedure and reacted with N ‐bromosuccinimide (NBS) in the presence of a catalytic amount of silver nitrate to give carbo[4]helicene‐ethynyl bromide 3 a in 77 % yield (Scheme , top). Compound 3 a was then subjected to Hsung conditions to form ynamide 4 a in a modest 26 % yield (unoptimized due to the very low solubility of 3 a ).…”
Section: Resultsmentioning
confidence: 99%
“…With the idea of increasing the complexity on this kind of supramolecular assemblies,A utschbach, Crassous,L escop, RØau et al reported in 2013 the preparation of multitopic 2,6-bis(aza [6]helicenephosphole)-pyridine (27)d isplaying au nique combination of (N,P, N,P, N )d onor atoms (Figure 8). [40] This ligand is well-structured to generate double stranded helicates in the presence of Cu I .T he existence of enantiopure M or P helicenes allowed the preparation of enantiopure helical ligands-named helicands-that generated double-stranded helicene-capped tetrametallic helicates upon coordination with Cu I .These helicates bear two pairs of Cu I dimers-displaying cuprophilic interactions,a salready seen in 6, 8a,b and in 25, 26-coordinated to the Natoms of both aza [6]helicene and pyridine connecting unit and bridged by the Patom of the phosphole.…”
Section: Coordination Of Multitopic Helicenic Ligands 241 Multitopmentioning
confidence: 99%
“…with bis-metallated building blocks of known geometry.I n 2014, RØau, Crassous,L escop,a nd co-workers reported the preparation of dissymmetrical U-shape p-stacked supramolecular assemblies using ab is-pyridyl-phosphole,c opper-(I) and monotopic p-conjugated helical ligands. [27] Theb is-2(2-pyridyl)-phosphole ligand 5 acted as an (N,P, N )tridentate ligand that-upon coordination with Cu I -generated pincerlike structure 6 holding aC u I dimer (Figure 2a,b). The addition of this system to monotopic [4]helicene derivatives (7a,b)e ndowed with cyano groups (having different linkers between the CN moiety and the [4]helicene,s ee Figure 2b) gave rise to the formation of symmetrical U-shaped complexes 8a,b shown in Figure 2c.I nt hese complexes,t he [4]helicene units display similar M or P stereochemistry in the solid state.T hese U-shaped complexes possess the ability to form head-to-tail supramolecular heterochiral dimers,w ith al arge portion of the ligands being involved in p-p interactions,a sd epicted in Figure 2d.I nt heir turn, the above-mentioned network of p-p interactions between the aromatic ligands inside the crystal promoted the formation of infinite columnar aggregates (see 8b in Figure 2e).…”
Section: Rafaelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Heck–Sonogashira sequences or the Suzuki–Miyaura reaction (between potassium alkynyl‐aryltrifluoroborates and aryl halides) are also useful for synthesizing such π‐conjugated molecules. The synthesis of similar polyaromatic molecules can also be achieved by Sonogashira coupling followed by Wadsworth–Emmons reaction using diethyl (4‐cyanobenzyl)phosphonate . The Heck–Sonogashira reaction sequence has also been reported but this yielded only non‐hydroxylated arylethenyl‐arylethynyl‐arene products .…”
Section: Introductionmentioning
confidence: 99%